Prevalence of peste des petits ruminants virus antibodies in sheep and goats sera from Central-Western Sudan - Safa E.M. Ali; Yassin A.M. Ahmed; Alwia A. Osman; Omiema A. Gamal Eldin; Nussieba A. Osman (Onderstepoort Journal of Veterinary Research, 2023)
Clinical signs suggestive of peste des petits ruminants (PPR) involved herds of small ruminants, which were described elsewhere in Sudan. Peste des petits ruminants was confirmed using an Immunocapture ELISA (IC-ELISA) assay in samples of infected and dead animals in areas of outbreaks. Therefore, to update information regarding the current situation and for assessment of the serological prevalence of PPR in small ruminants mingled at Central and Western Sudan during 2018–2019, 368 sera were collected from sheep (325 sera) and goats (43 sera) with different ages and breeds. These sera included 186 sera (173 sheep and 13 goats) from White Nile State and 182 sera (152 sheep and 30 goats) from Kordofan States. Competitive ELISA demonstrated higher prevalence of PPRV antibodies of 88.9%, 90.7% and 88.6% in both sheep and goats, goats, and sheep sera, respectively. Moreover, 100%, 94.7% and 78.5% seroprevalence values were demonstrated in South Kordofan, North Kordofan and White Nile States. The higher seroprevalence values detected in sera of unvaccinated sheep and goats indicated the wide exposure of these animals to PPRV and presence of protection following PPR viral infection. The findings of the study indicated that PPR is endemic in the surveyed areas of Sudan.